Efficacy of sacubitril/valsartan among patients with chronic heart failure with reduced ejection fraction - Madiha Butt; Ayesha Niazi; Zahra Rafique; Nadia Shams; Lubna Meraj; Asma Rauf (Journal of Rawalpindi Medical College)
Objective: Chronic heart failure is one of the leading causes of hospitalization and recurrent admissions among the elderly population worldwide. This study was conducted to determine the efficacy of Sacubitril/Valsartan among heart failure cases with reduced left ventricular ejection fraction.